NATIONAL IDENTITY AND RELATIONSHIP IN THE INFORMATION SOCIETY (Conference Zone, 2022)
The article scientifically analyzes the relationship between the information society and national identity. This is a neo-conservative doctrine that serves to strengthen the positive qualities of national self-consciousness and represents the protection of national interests, national mentality, spiritual maturity, and national "I". The article scientifically substantiates that the ideology of Uzbekistan, which has the function of national ideology, is a philosophical theory that serves rational, constructive changes, democratization and modernization of society.